2021
DOI: 10.1002/htj.22135
|View full text |Cite
|
Sign up to set email alerts
|

Cattaneo–Christov double‐diffusion model with Stefan blowing effect on copper–water nanofluid flow over a stretching surface

Abstract: We often encounter many processes where the cooling rate is a key factor in deciding the features of a desired product. Due to increasing demands of controlled cooling systems, an effort is made to theoretically study the effect of volume fraction on mixed convective Cu–water nanofluid flow over a stretching surface with activation energy and thermal radiation. The nonlinear dynamical system is simplified using apt similarity variables and the obtained ordinary differential equations are dealt numerically usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The thermophoresis along with random motion characteristics of radiative Casson fluid flow, including gyrotactic microorganisms driven by a moving wedge, has been acknowledged by Raju et al 6 They found that thermal and concentration profiles are boosted by the escalating value of thermophoresis parameter, whereas Brownian motion parameter showed a reverse trend for the thermal boundary layer. Recently, many researchers have explored the influences of random motion features of nanosized particles and thermophoresis on the flow of nanofluid using Buongiorno's model at different geometries 7–15 . Although, recent years have observed the rise in the number of investigators exploring the flow and heat transfer problems utilizing wedge surfaces due to its assorted feasible functions in the area of manufacturing, high‐speed thermal aerodynamics, fiber technology, nuclear cooling system, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The thermophoresis along with random motion characteristics of radiative Casson fluid flow, including gyrotactic microorganisms driven by a moving wedge, has been acknowledged by Raju et al 6 They found that thermal and concentration profiles are boosted by the escalating value of thermophoresis parameter, whereas Brownian motion parameter showed a reverse trend for the thermal boundary layer. Recently, many researchers have explored the influences of random motion features of nanosized particles and thermophoresis on the flow of nanofluid using Buongiorno's model at different geometries 7–15 . Although, recent years have observed the rise in the number of investigators exploring the flow and heat transfer problems utilizing wedge surfaces due to its assorted feasible functions in the area of manufacturing, high‐speed thermal aerodynamics, fiber technology, nuclear cooling system, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The innovative feature of this project is the use of a modified Buongiorno type to account for Brownian motion, thermophoresis, and volume fraction for nanofluids. An attempt was undertaken to theoretically explore the influence of volume fraction on a mixed convective Cu-water nanofluid flow across a stretching surface with activation energy and thermal radiation, due to the growing demand for regulated cooling systems 12 . The influences of mixed convection, thermal radiation, and chemical reaction were numerically investigated for the steady Cu-water nanofluid flow in the presence of a magnetic field 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Rawat and Kumar 40 studied the copper water nanofluid with the utilization of Cattaneo–Christov heat flux model. The double‐diffusion copper–water nanofluid flow model with the employment of Cattaneo–Christov scheme and Stefan blowing has been discussed by Negi et al 41 . The nanofluid flow over a vertical Riga plate is studied by Sawan et al 42 .…”
Section: Introductionmentioning
confidence: 99%